On the optimality of J. Cheeger and P. Buser inequalities - Colbois, Bruno; Matei, Ana-Maria (My University, 2003)
We study the relationship between the first eigenvalue of the Laplacian and Cheeger constant when the Cheeger constant converges to zero, in the case of compact Riemannian manifolds and of finite graphs. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: eigenvalue; Laplacian; Cheeger constant; asymptotic behaviour